1996
DOI: 10.1029/96jc00463
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the diurnal cycle of carbon monoxide: Sensitivity to physics, chemistry, biology, and optics

Abstract: As carbon monoxide within the oceanic surface layer is produced by solar radiation, diluted by mixing, consumed by biota, and outgassed to the atmosphere, it exhibits a diurnal cycle. The effect of dilution and mixing on this cycle is examined using a simple model for production and consumption coupled to three different mixed layer models. The magnitude and timing of the peak concentration, the magnitude of the average concentration, and the air-sea flux are considered. The models are run through a range of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Our data indicate that the variations in the diurnal pattern of sea surface COS are related to the combined effects of both UV light and wind-induced vertical mixing, with lowest COS concentrations accompanied by high wind speeds and low light levels. Downward mixing at high wind speeds would tend to reduce both sea surface concentration and diel amplitude of dissolved COS (Ferek and Andreae, 1984;Ulshrfer et al, 1995), as has been suggested by several modeling studies of COS (Doney et aL, 1995;Najjar et al, 1995) and CO (Gnanadesikan, 1996), which like COS is produced photochemically in sea surface water. Overall, our observations are consistent with the idea that photoproduction, hydrolysis removal, and wind-induced downward mixing are key factors controlling the biogeochemical cycling of sea surface COS (Andreae and Ferek, 1992;Ferek and Andreae, 1984;Ulshrfer et al, 1996;Ulsh6fer et al, 1995).…”
Section: Study Area Descriptionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our data indicate that the variations in the diurnal pattern of sea surface COS are related to the combined effects of both UV light and wind-induced vertical mixing, with lowest COS concentrations accompanied by high wind speeds and low light levels. Downward mixing at high wind speeds would tend to reduce both sea surface concentration and diel amplitude of dissolved COS (Ferek and Andreae, 1984;Ulshrfer et al, 1995), as has been suggested by several modeling studies of COS (Doney et aL, 1995;Najjar et al, 1995) and CO (Gnanadesikan, 1996), which like COS is produced photochemically in sea surface water. Overall, our observations are consistent with the idea that photoproduction, hydrolysis removal, and wind-induced downward mixing are key factors controlling the biogeochemical cycling of sea surface COS (Andreae and Ferek, 1992;Ferek and Andreae, 1984;Ulshrfer et al, 1996;Ulsh6fer et al, 1995).…”
Section: Study Area Descriptionmentioning
confidence: 95%
“…Our kinetic box model considers the effect of vertical mixing implicitly by adjusting the in situ photoproduction constant to the prevailing conditions. A potential improvement would be to link our kinetic model to a physical model, which accounts for the diel cycle of turbulent transport within the upper mixed layer of the ocean (Doney et al, 1995;Gnanadesikan, 1996;Kantha and Clayson, 1994).…”
Section: (I) --Dmix Ao Kddmi~xmentioning
confidence: 99%
“…As a short-lived photoproduct, CO is a key species for modeling the couplings among optics, photochemistry, biology, mixing dynamics and gas exchange in the upper ocean (Kettle 1994, Doney et al 1995, Gnanadesikan 1996, Najjar et al 2003. Moreover, photoproduction of CO itself is important, since CO is the second most abundant carbon-containing product of CDOM photochemistry, with a yield higher than the sum of all the known photochemically produced organic compounds (Mopper et al 1991).…”
Section: Abstract: Carbon Monoxide · Microbial Consumption · Wright-mentioning
confidence: 99%
“…First evidence for a predominantly photochemical CO source in seawater came from observations of a pronounced diurnal cycle in sea-surface CO concentrations. These observations were later explained by the interplay between a strong photoproduction term (Wilson et al, 1970;Redden, 1982;Bullister et al, 1982;Gammon and Kelly, 1990;Zuo and Jones, 1995;Zafiriou et al, 2003) and fast removal by microbial oxidation Seiler, 1980, 1982;Zafiriou et al, 2003), although air-sea gas exchange Erickson, 1989;Bates et al, 1995;Zuo and Stubbins et al, 2006) and downward mixing (Kettle, 1994(Kettle, , 2005Doney et al, 1995;Najjar et al, 1995;Gnanadesikan, 1996;Johnson and Bates, 1996) also may be important. These interactions between biogeochemical and physical processes lead to complex spatial and temporal patterns in CO cycling that still pose a challenge today.…”
Section: Introductionmentioning
confidence: 99%
“…Current best estimates of the combined strength of the dissolved organic carbon sink associated with DOM photodegradation are in the order of 10-30% of global oceanic primary production (Miller and Moran, 1997;Mopper and Kieber, 2000), clearly relevant on Global scales. Furthermore, CO has also emerged as a key tracer for use in testing and tuning models of other mixed-layer processes, including photochemistry, ocean optics, radiative flux, mixing and air-sea gas exchange (Kettle, 1994(Kettle, , 2005Doney et al, 1995;Najjar et al, 1995;Gnanadesikan, 1996;Johnson and Bates, 1996). Hence, improved modelling and quantification of marine CO photoproduction will contribute to our understanding of a variety of interconnected marine biogeochemical processes.…”
Section: Introductionmentioning
confidence: 99%